Perbandingan Properti Psikometris Skala Kesehatan Mental (SKM) antara Metode Administrasi Paper-and-Pencil dan Web-Based - Mikael Reno Prasasto; Wahyu Widhiarso (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2016)
Advancements on information technology had helped scientific development.For example, now we could present a test using computers rather than using printedpapers. This research compares the differences between the psychometric properties of apaper-and-pencil test (PPT) and web-based test (WBT). This research used Skala KesehatanMental (SKM) which was given to 544 junior and senior high-school grade school. Thescale has 32 items and administered with either paper or on a website. The result showedthat each method has a different but not significant psychometric properties. Compared toPPT, WBT was able to deliver fewer cases of outliers and higher item-total correlation.Reliability coefficient on both method were satisfying and able to stay unidimensional onfactor analysis. Item endorsability does not appear to have significant differences. Moreresearch on this topic is needed to further examine the effect between each method on testresults.